Coping under stress: prefrontal control predicts stress burden during the COVID-19 crisis - Monninger, Maximilian; Pollok, Tania; Aggensteiner, Pascal; Kaiser, Anna; Reinhard, Iris; Hermann, Andrea; Meyer-Lindenberg, Andreas; Brandeis, Daniel; Banaschewski, Tobias; Holz, Nathalie E. (European neuropsychopharmacology, 2022)
The coronavirus (COVID-19) pandemic has confronted millions of people around the world with an unprecedented stressor, affecting physical and mental health. Accumulating evidence suggests that emotional and cognitive self-regulation is particularly needed to effectively cope with stress. Therefore, we investigated the predictive value of affective and inhibitory prefrontal control for stress burden during the COVID-19 crisis. Physical and mental health burden were assessed using an online survey, which was administered to 104 participants of an ongoing at-risk birth cohort during the first wave in April 2020. Two follow-ups were carried out during the pandemic, one capturing the relaxation during summer and the other the beginning of the second wave of the crisis. Prefrontal activity during emotion regulation and inhibitory control were assessed prior to the COVID-19 crisis. Increased inferior frontal gyrus activity during emotion regulation predicted lower stress burden at the beginning of the first and the second wave of the crisis. In contrast, inferior and middle frontal gyrus activity during inhibitory control predicted effective coping only during the summer, when infection rates decreased but stress burden remained unchanged. These findings remained significant when controlling for sociodemographic and clinical confounders such as stressful life events prior to the crisis or current psychopathology. We demonstrate that differential stress-buffering effects are predicted by the neural underpinnings of emotion regulation and cognitive regulation at different stages during the pandemic. These findings may inform future prevention strategies to foster stress coping in unforeseen situations. (C) 2021 The Author(s). Published by Elsevier B.V.
Gesehen am 16.02.2022